Barium hafnium oxide-based nano-ceramic powder and its preparation method and application

By preparing barium hafnate-based nanoceramic powder and doping with Cu, Bi, Re and other elements, the high melting point and difficult sintering problems of barium hafnate-based ceramics are solved, and electrolytes with high sintering activity and high conductivity are achieved, which is suitable for large-scale production and improves electrical properties.

CN119241232BActive Publication Date: 2025-03-18SHANDONG GUIYUAN NEW MATERIAL TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411773325.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The high melting point, difficulty in sintering and volatilization of Ba elements of existing barium hafnate-based ceramics lead to uneven chemical components and reduced conductivity.

Method used

A preparation method of barium hafnate-based nanoceramic powder is adopted to prepare nanopowders with high sintering activity, high dispersion and uniform grain size through steps such as batching, grinding, washing, drying and microwave calcining. The sintering temperature and grain boundary resistance are reduced by doping elements such as Cu, Bi, and Re.

Benefits of technology

Low-temperature sintering, uniform grains and high conductivity of barium hafnate-based electrolyte are achieved, suitable for large-scale production, and the electrical properties of solid oxide fuel cell electrolytes are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241232B_ABST
    Figure CN119241232B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of ceramic powders and their preparation and application, and specifically relates to barium hafnate-based nano-ceramic powders and their preparation method and application. The barium hafnate-based nano-ceramic powders of the present invention have a chemical formula of BaHf x Cu y Bi z Re 1‑x‑y‑z O 3‑δ . The preparation method of the barium hafnium oxide-based nano-ceramic powder comprises the following steps: mixing a metal salt, sodium carbonate or sodium hydroxide, and lignin powder, grinding to obtain a precursor; washing with water and then with anhydrous ethanol, filtering; microwave drying the precipitate obtained by filtration, and microwave calcining the obtained powder to obtain a ceramic powder. The present invention provides a barium hafnium oxide-based nano-ceramic powder having the characteristics of high dispersibility, and the present invention also provides a preparation method thereof, which has a simple process and high production efficiency. The ceramic nano-powder prepared by the present invention is used to prepare an electrolyte, which is applied to a solid oxide fuel cell electrolyte to improve its electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic powders and preparation and application thereof, and specifically relates to barium hafnium oxide-based nano ceramic powders and a preparation method and application thereof. Background Art

[0002] Rare earth element doped barium hafnium oxide (BaHfO3) ceramics have excellent chemical stability against CO2 and H2O and are a new type of solid oxide fuel cell electrolyte, but their high melting point and difficulty in sintering (sintering temperature ≥ 1600°C, insulation time ≥ 10h) greatly limit their practical applications. What is even more tricky is that during the high-temperature calcination process, the Ba element is easily volatilized, which not only causes the chemical composition to deviate from the ideal stoichiometric ratio, but also directly causes a significant decrease in conductivity. In addition, the grain boundary resistance of this type of electrolyte is also one of the key factors restricting the improvement of conductivity. Therefore, how to lower the sintering temperature, reduce the grain boundary resistance, and increase the ionic conductivity is the key to preparing high-performance barium hafnium oxide-based electrolytes.

[0003] Improving the sintering activity of raw materials by synthesizing nanopowders is an effective way to reduce the sintering temperature. CN103467085A uses BaCO3, TiO2, and HfO2 as raw materials and adopts a solid phase reaction method to prepare barium hafnate powder and barium hafnate-based piezoelectric ceramics, but the solid phase reaction method cannot obtain nanopowders, which further limits its application. CN101239822A uses barium nitrate, hafnium oxychloride, and cerium nitrate as raw materials and adopts a coprecipitation method to prepare barium hafnate nanopowder doped with rare earth cerium. However, during the coprecipitation process, the solution concentration gradually decreases, the reaction system is unstable, and it is easy to cause uneven grain size. In addition, the process flow is complicated and the production efficiency is low.

[0004] In addition, adding sintering aids is another effective way to reduce the firing temperature. However, sintering aids are easily enriched at the grain boundaries, resulting in an increase in the grain boundary resistance of the electrolyte, which in turn leads to a decrease in conductivity. For example, the prior art uses oxides or hydroxides of barium, hafnium, and cerium as starting materials and uses a solid phase synthesis method to prepare BaHfO3:Ce nanopowders, but the element distribution at the atomic scale is uneven. There is also prior art that improves the ionic conductivity of the electrolyte by doping with Bi2O3, and uses an oxygen ion-proton mixed electrolyte preparation method, but the solid phase method used does not obtain nanopowders. In "Ceramics International", Sun Haibin, Guo Xue, Yu Fangyong, et al. Enhanced sinterability and electrical performance of Sm2O3doped CeO2 / BaCeO3electrolytes for intermediate-temperature solid oxide fuel cells through Bi2O3co-doping, Ceramics International 45 (2019) 7667–7672) Bi2O3 and Sm2O3 co-doped CeO2 / BaCeO3 nanopowders were prepared by combustion method, which improved the sintering performance of the electrolyte. However, the bismuth nitrate in the raw material used is unstable in aqueous solution and easily decomposes into basic salts, resulting in uneven element distribution. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art, provide a barium hafnate-based nano-ceramic powder, which has the characteristics of high sintering activity, high dispersibility, and uniform grain size. The present invention also provides a preparation method thereof, which has simple process, energy saving and environmental protection, high production efficiency, and is suitable for mass production. The ceramic nano-powder prepared by the present invention is used to prepare an electrolyte, which is applied to a solid oxide fuel cell electrolyte to improve its electrical performance.

[0006] The barium hafnate-based nano-ceramic powder of the present invention has a chemical formula of BaHf x Cu y Bi z Re 1-x-y-z O 3-δ , where x, y, z>0, Re is a rare earth element, and δ is the oxygen vacancy content formed by element doping. When there are multiple rare earth elements, their subscripts are the same.

[0007] The method for preparing the barium hafnium oxide-based nano-ceramic powder comprises the following steps:

[0008] S1 ingredients: according to BaHf x Cuy Bi z Re 1-x-y-z O 3-δ Weigh metal salts of Ba, Hf, Cu, Bi and Re in a stoichiometric ratio, weigh sodium carbonate or sodium hydroxide at 2 to 4 times the molar number of the metal salt, and weigh lignin powder at 1 to 5% of the mass fraction of the metal salt;

[0009] S2, grinding: mixing metal salt, sodium carbonate or sodium hydroxide, and lignin powder, and grinding to obtain a paste precursor;

[0010] S3 washing: first wash with water and then with anhydrous ethanol, and filter;

[0011] S4 drying: drying the precipitate obtained by suction filtration with microwave to obtain a powder;

[0012] S5 calcination: calcining the powder with microwave to obtain barium hafnium oxide-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ .

[0013] The metal salts of Ba, Hf, Cu, Bi and Re in S1 are barium nitrate, hafnium oxychloride, copper nitrate trihydrate, bismuth nitrate and rare earth nitrate.

[0014] The weight average molecular weight of the lignin powder in S1 is 800-1200, and the median particle size is 0.05-0.3 μm.

[0015] The grinding method in step S2 is dry grinding, and the grinding time is 0.5-3h.

[0016] In step S3, the number of water washings is 3-5 times; the number of anhydrous ethanol washings is 1-3 times.

[0017] In step S4, the microwave drying frequency is 1-2.45 GHz, and the drying time is 30-90 min.

[0018] The microwave calcination system in step S5 is: first, heating to 400-600°C at 3-5°C / min, and keeping warm for 1-3h; then heating to 800-900°C at 4-10°C / min, and keeping warm for 3-6h. Since hafnium oxide has good microwave absorption properties during microwave calcination, the microwave calcination process can reduce the sintering activation energy, thereby effectively reducing the crystallization phase temperature.

[0019] The application of the barium hafnate-based nano-ceramic powder is as follows: the barium hafnate-based nano-ceramic powder is pressed into a green body, and powders of the same component are buried on one side of the green body, with the powder coverage being 1-2 times the weight of the green body. The green body is subjected to electric heating and calcination to obtain a barium hafnate-based electrolyte, which is mainly used as a solid oxide fuel cell electrolyte.

[0020] The electric heating calcination temperature is 1150-1350°C, the heating rate is 1-5°C / min, and the heat preservation time is 2-10h.

[0021] Specifically, the barium hafnate-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ The preparation method comprises the following steps:

[0022] S1 ingredients: according to BaHf x Cu y Bi z Re 1-x-y-z O 3-δ Barium nitrate, hafnium oxychloride, copper nitrate trihydrate, bismuth nitrate and rare earth nitrate are weighed in a stoichiometric ratio, sodium carbonate or sodium hydroxide is weighed according to 2 to 4 times the molar number of the metal salt, and lignin powder is weighed according to 1 to 5% of the mass fraction of the metal salt.

[0023] S2 grinding: Mix the metal salt, sodium carbonate or sodium hydroxide, and lignin powder, and dry grind for 0.5-3h to obtain a paste precursor.

[0024] S3 washing: wash the precursor 3-5 times with deionized water to obtain a precipitate; wash the precipitate 1-3 times with anhydrous ethanol and filter it.

[0025] S4 Drying: Dry the precipitate obtained by filtration at 1-2.45 GHz microwave for 30-90 min to obtain a powder.

[0026] S5 calcination: calcine the powder by microwave, raise the temperature to 400-600℃ at 3-5℃ / min, keep it warm for 1-3h; then raise the temperature to 800-900℃ at 4-10℃ / min, keep it warm for 3-6h, and obtain barium hafnium oxide-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ .

[0027] The barium hafnium oxide-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-zO 3-δ Application: Nano powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ The green body is pressed into a disc-shaped body, one side of which is buried with 1-2 times the weight of powder of the same component, and placed in a box furnace for electric heating calcination at a temperature of 1150-1350°C, a heating rate of 1-5°C / min, and a holding time of 2-10h to obtain a dense barium hafnium oxide-based electrolyte.

[0028] The barium hafnium oxide-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ The preparation method adopts a metal salt and sodium carbonate (or sodium hydroxide) to undergo a chemical reaction during dry grinding, and the reaction rate is controllable, which is conducive to obtaining nanoparticles with uniform grain size. Moreover, the grinding process does not require an aqueous medium, which effectively avoids the problem that bismuth nitrate is easily decomposed into a basic salt in an aqueous solution. The present invention adds lignin to the precursor as a pore-forming agent, making it insoluble in water but soluble in ethanol, and the lignin is evenly distributed inside the precursor during the grinding and mixing process, can stably exist during the deionized water washing process, and is removed during the anhydrous ethanol washing process, thereby forming pores inside the precursor. For lignin that is not removed cleanly, it will also escape in the form of CO2 and water vapor during the precursor calcination process.

[0029] The barium hafnium oxide-based nano ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ The preparation method utilizes the low melting point and high oxygen ion conductivity of bismuth oxide to dope Bi element into the barium hafnium oxide-based electrolyte, which can reduce the sintering temperature on the one hand and significantly improve the conductivity on the other hand. Cu doping can promote the grain growth of the barium hafnium oxide-based electrolyte during the sintering process, which is beneficial to reduce the number of grain boundaries. It also has a significant grain boundary cleaning effect and can effectively reduce the adverse effect of grain boundary resistance on conductivity. Re, Bi, and Cu multi-element co-doping is beneficial to increase the oxygen vacancy concentration and improve the overall electrical properties of the barium hafnium oxide-based electrolyte.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The barium hafnium oxide-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O3-δ The preparation method adds lignin to effectively improve the dispersibility of the powder and solves the problem of easy agglomeration of nanopowders. The synthesis process is simple, the production efficiency is high, the energy saving and environmental protection are high, and it is easy to industrialize.

[0032] (2) Barium hafnium oxide-based nano-ceramic powder BaHf prepared by the method of the present invention x Cu y Bi z Re 1-x-y-z O 3-δ , uniform particle size.

[0033] (3) The barium hafnium oxide-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ It is used to prepare electrolytes with excellent electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The BaHf prepared in Example 1 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ X-ray diffraction pattern of powder;

[0035] Figure 2 The BaHf prepared in Example 1 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ Microscopic morphology of powder;

[0036] Figure 3 The BaHf prepared in Example 1 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ Microscopic morphology of the electrolyte cross section;

[0037] Figure 4 The BaHf prepared in Example 1 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ Microscopic morphology of the electrolyte surface;

[0038] Figure 5 BaHf prepared in Comparative Example 1 0.6 Sm 0.4 Microscopic morphology of the cross section of O3 electrolyte;

[0039] Figure 6 BaHf prepared in Comparative Example 1 0.6 Sm 0.4 Microscopic morphology of the O3 electrolyte surface;

[0040] Figure 7 BaHf prepared in Comparative Example 2 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ Microscopic morphology of powder. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with specific embodiments.

[0042] The raw materials and additives used in the following examples and comparative examples are all commercially available products.

[0043] Example 1

[0044] The nano ceramic powder BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The preparation method comprises the following steps:

[0045] S1 ingredients: according to BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The stoichiometric ratio was 26.14 g of barium nitrate, 24.57 g of hafnium oxychloride, 2.42 g of copper nitrate trihydrate, 3.95 g of bismuth nitrate, 8.45 g of samarium nitrate hexahydrate, 53.00 g of sodium carbonate, and 1.31 g of lignin powder with a weight-average molecular weight of 1000 and a median particle size of 0.05 μm.

[0046] S2 grinding: barium nitrate, hafnium oxychloride, copper nitrate trihydrate, bismuth nitrate, samarium nitrate hexahydrate, sodium carbonate, and lignin powder are mixed and dry-grinded for 1 hour to obtain a paste precursor.

[0047] S3 washing: washing the precursor with deionized water for 4 times to obtain a precipitate; washing the precipitate with anhydrous ethanol for 2 times.

[0048] S4 drying: the precipitate was dried by microwave, the microwave drying frequency was 1.5 GHz, and the drying time was 80 min.

[0049] S5 calcination: The dried powder was calcined by microwave, firstly, the temperature was raised to 500°C at 3°C / min and kept at this temperature for 2h; then the temperature was raised to 880°C at 6°C / min and kept at this temperature for 6h to obtain nano ceramic powder BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The X-ray diffraction pattern of the powder is as follows Figure 1 As shown by Figure 1 It can be seen that BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The powder has a pure phase perovskite structure. The microscopic morphology of the powder is shown in the figure below: Figure 2 As shown by Figure 2 It can be seen that BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The average particle size of the powder is 30-60nm, showing good dispersibility.

[0050] The above nano ceramic powder BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The following applications were performed: a round sheet was pressed into a green body, powders of the same composition were buried on one side of the green body, and the green body was placed in a box furnace for electric heating and calcination. The temperature was raised to 1300°C at a heating rate of 3°C / min and kept at this temperature for 5 hours to obtain a dense BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ Electrolyte, the microscopic morphology of the cross section of the electrolyte is as follows Figure 3 As shown by Figure 3 It can be seen that the cross section has no obvious pores and presents a dense structure. The microscopic morphology of the surface of the electrolyte is shown in Figure 4 As shown by Figure 4 It can be seen that the average grain size of the electrolyte is about 6 μm.

[0051] The nano ceramic powder BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The electrolyte was tested by Archimedes drainage method. The relative density of the electrolyte was 98%. The conductivity was 1.6×10 -2S cm -1 .

[0052] Comparative Example 1

[0053] A kind of BaHf 0.6 Sm 0.4 O 3-δ The preparation process of the nanopowder is exactly the same as that of Example 1, except that Bi and Cu elements are not doped, and the nitrate ratio is: 26.14 g of barium nitrate, 20.48 g of hafnium oxychloride, and 16.90 g of samarium nitrate hexahydrate, and the ratios of other raw materials remain unchanged.

[0054] The prepared BaHf 0.6 Sm 0.4 O 3-δ The nanopowder was prepared by the same application steps as in Example 1 to obtain BaHf 0.6 Sm 0.4 O 3-δ Electrolyte, the microscopic morphology of the cross section of the electrolyte is as follows Figure 5 As shown by Figure 5 It can be seen that there are a lot of pores in the cross section of the electrolyte. Using the Archimedes drainage method to test, its relative density is only 79%; the microscopic morphology of the surface of the electrolyte is shown in Figure 6 As shown by Figure 6 It can be seen that the average grain size of the electrolyte surface is less than 1 μm, and the conductivity is only 0.3×10 -3 S cm -1 .

[0055] By comparing the above Example 1 and Comparative Example 1, it can be seen that by co-doping Cu and Bi into the barium hafnate-based nanopowder, a dense structure can be obtained at 1300°C, which significantly improves the sintering performance of the barium hafnate-based electrolyte. At the same time, the average grain size of the electrolyte is increased from <1μm to about 6μm. On the one hand, the adverse effect of pores on conductivity is reduced, and on the other hand, the number of grain boundaries is reduced by increasing the grain size, thereby reducing the adverse effect of grain boundary resistance on conductivity, thereby obtaining excellent electrical properties.

[0056] Comparative Example 2

[0057] A kind of BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The preparation process of the nanopowder is exactly the same as that of Example 1, except that lignin is not added. The raw material ratio is: 26.14g barium nitrate, 24.57g hafnium oxychloride, 2.42g copper nitrate trihydrate, 3.95g bismuth nitrate, 8.45g samarium nitrate hexahydrate, and 53.00g sodium carbonate is weighed.

[0058] The prepared BaHf 0.6 Cu 0.1 Bi 0.1 Sm 0.2 O 3-δ The microscopic morphology of the powder is shown in Figure 7 As shown. It can be seen that the nanopowder has poor dispersibility and serious agglomeration between particles. By comparing Example 1 and Comparative Example 2, it can be seen that lignin can significantly improve the dispersibility of the powder. The reason is that lignin helps to form pores between the powder particles. On the one hand, lignin exists stably during the water washing process, and during the anhydrous ethanol washing process, part of the lignin is removed due to dissolution in anhydrous ethanol, forming pores inside the precursor; on the other hand, the residual lignin escapes in the form of CO2 and water vapor during the calcination process, further forming pores. Due to the poor dispersibility of the powder, its sintering activity is low, the relative density of the electrolyte is only 91%, and the conductivity under 700°C wet air test conditions is 0.9×10 -2 S cm -1 .

[0059] Example 2

[0060] The nano ceramic powder BaHf 0.7 Cu 0.1 Bi 0.1 Ce 0.1 O 3-δ The preparation method comprises the following steps:

[0061] S1 ingredients: according to BaHf 0.7 Cu 0.1 Bi 0.1 Ce 0.1 O 3-δ According to the stoichiometric ratio, 26.14 g of barium nitrate, 28.67 g of hafnium oxychloride, 2.42 g of copper nitrate trihydrate, 3.95 g of bismuth nitrate, and 4.34 g of cerium nitrate hexahydrate were weighed. 11.97 g of sodium hydroxide and 1.50 g of lignin powder with a weight average molecular weight of 800 and a median particle size of 0.15 μm were weighed.

[0062] S2 grinding: barium nitrate, hafnium oxychloride, copper nitrate trihydrate, bismuth nitrate, cerium nitrate hexahydrate, sodium hydroxide, and lignin powder are mixed and dry-grinded for 2 hours to obtain a paste precursor.

[0063] S3 washing: washing the precursor with deionized water for 5 times to obtain a precipitate; washing the precipitate with anhydrous ethanol for 3 times.

[0064] S4 drying: The precipitate was dried by microwave, the microwave drying frequency was 2 GHz, and the drying time was 60 min.

[0065] S5 calcination: The dried powder was calcined by microwave. First, the temperature was raised to 600°C at 4°C / min and kept at this temperature for 2 h; then the temperature was raised to 900°C at 6°C / min and kept at this temperature for 4 h to obtain nano-ceramic powder BaHf 0.7 Cu 0.1 Bi 0.1 Ce 0.1 O 3-δ .

[0066] The above nano ceramic powder BaHf 0.7 Cu 0.1 Bi 0.1 Ce 0.1 O 3-δ The following applications were performed: a round sheet was pressed into a green body, 1.5 times the weight of the same component powder was buried on one side of the green body, and the green body was placed in a box furnace for electric heating and calcination. The temperature was raised to 1250°C at a heating rate of 5°C / min and kept at this temperature for 5h to obtain a dense BaHf 0.7 Cu 0.1 Bi 0.1 Ce 0.1 O 3-δ Electrolytes.

[0067] The powder has good dispersibility. The relative density of the electrolyte is 97% and the conductivity is 1.5×10 -2 S cm -1 .

[0068] Example 3

[0069] The nano ceramic powder BaHf 0.5 Cu 0.15 Bi 0.15 Dy 0.1 Nd 0.1 O 3-δ The preparation method comprises the following steps:

[0070] S1 ingredients: according to BaHf 0.5 Cu 0.15 Bi 0.15 Dy 0.1 Nd 0.1 O 3-δ The stoichiometric ratio was 26.14 g of barium nitrate, 20.48 g of hafnium oxychloride, 3.62 g of copper nitrate trihydrate, 5.92 g of bismuth nitrate, 4.57 g of dysprosium nitrate hexahydrate, 4.38 g of neodymium nitrate hexahydrate, 37.10 g of sodium carbonate, and 1.10 g of lignin powder with a weight average molecular weight of 1200 and a median particle size of 0.1 μm.

[0071] S2 grinding: barium nitrate, hafnium oxychloride, copper nitrate trihydrate, bismuth nitrate, dysprosium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium carbonate, and lignin powder are mixed and dry-grinded for 3 hours to obtain a paste precursor.

[0072] S3 washing: washing the precursor with deionized water for 3 times to obtain a precipitate; washing the precipitate with anhydrous ethanol for 2 times.

[0073] S4 drying: the precipitate was dried by microwave, the microwave drying frequency was 2.45 GHz, and the drying time was 40 min.

[0074] S5 calcination: The dried powder was calcined by microwave. First, the temperature was raised to 550°C at 5°C / min and kept at this temperature for 2.5h; then the temperature was raised to 800°C at 4°C / min and kept at this temperature for 6h to obtain nano-ceramic powder BaHf 0.5 Cu 0.15 Bi 0.15 Dy 0.1 Nd 0.1 O 3-δ .

[0075] The above BaHf 0.5 Cu 0.15 Bi 0.15 Dy 0.1 Nd 0.1 O 3-δ The following applications were performed: a round sheet was pressed into a green body, and two times the weight of the same component powder was buried on one side of the green body. The green body was placed in a box furnace for electric heating, and the temperature was raised to 1200°C at a heating rate of 3°C / min and kept at this temperature for 6 hours to obtain a dense BaHf 0.5 Cu 0.15 Bi 0.15 Dy 0.1 Nd 0.1 O 3-δ Electrolytes.

[0076] The relative density of the electrolyte was tested to be 98%, and the conductivity was 1.7×10 -2 Scm -1 .

Claims

1. A barium hafnium oxide-based nano-ceramic powder, characterized in that: The chemical formula is BaHf x Cu y Bi z Re 1-x-y-z O 3-δ , where x, y, z>0, Re is a rare earth element, and δ is the oxygen vacancy content formed by element doping; The barium hafnate-based nano-ceramic powder is prepared by the following preparation method: S1 ingredients: according to BaHf x Cu y Bi z Re 1-x-y-z O 3-δ Weigh metal salts of Ba, Hf, Cu, Bi and Re in a stoichiometric ratio, weigh sodium carbonate or sodium hydroxide at 2 to 4 times the molar number of the metal salt, and weigh lignin powder at 1 to 5% of the mass fraction of the metal salt; S2 grinding: mixing and grinding the metal salt, sodium carbonate or sodium hydroxide, and lignin powder to obtain a precursor; S3 washing: first wash with water and then with anhydrous ethanol, and filter; S4 drying: drying the precipitate obtained by suction filtration with microwave to obtain a powder; S5 calcination: calcining the powder with microwave to obtain barium hafnium oxide-based nano-ceramic powder BaHf x Cu y Bi z Re 1-x-y-z O 3-δ .

2. The barium hafnium oxide-based nano-ceramic powder according to claim 1, characterized in that: The metal salts of Ba, Hf, Cu, Bi and Re in S1 are barium nitrate, hafnium oxychloride, copper nitrate trihydrate, bismuth nitrate and rare earth nitrate.

3. The barium hafnium oxide-based nano-ceramic powder according to claim 1, characterized in that: The weight average molecular weight of the lignin powder in S1 is 800-1200, and the median particle size is 0.05-0.3 μm.

4. The barium hafnate-based nano-ceramic powder according to claim 1, characterized in that: The grinding method in step S2 is dry grinding, and the grinding time is 0.5-3h to obtain a paste precursor.

5. The barium hafnium oxide-based nano-ceramic powder according to claim 1, characterized in that: The number of water washing in step S3 is 3-5 times; The number of washing times with anhydrous ethanol is 1-3 times.

6. The barium hafnate-based nano-ceramic powder according to claim 1, characterized in that: In step S4, the microwave drying frequency is 1-2.45 GHz, and the drying time is 30-90 min.

7. The barium hafnium oxide-based nano-ceramic powder according to claim 1, characterized in that: The microwave calcination system in step S5 is as follows: first, heating to 400-600°C at 3-5°C / min and keeping warm for 1-3h; then heating to 800-900°C at 4-10°C / min and keeping warm for 3-6h.

8. An application of the barium hafnium oxide-based nano-ceramic powder according to claim 1, characterized in that: The barium hafnate-based nano-ceramic powder is pressed into a green body, and powders of the same component are buried on one side of the green body, with the powder coverage being 1-2 times the weight of the green body. The green body is then electrically heated and calcined to obtain a barium hafnate-based electrolyte.

9. The use of the barium hafnium oxide-based nano-ceramic powder according to claim 8, characterized in that: The electric heating calcination temperature is 1150-1350°C, the heating rate is 1-5°C / min, and the heat preservation time is 2-10h.

Citation Information

Patent Citations

  • Method for preparing rare earth cerium doping barium hafnate ceramic scintillator

    CN101239822A

  • Barium hafnium titanate leadless piezoelectric ceramic with high piezoelectric coefficient and preparation method of leadless piezoelectric ceramic

    CN103467085A

  • Spray coating method for producing dielectric ceramic powder body and obtained products thereof

    CN101314545A

  • Potassium-sodium niobate base lead-free piezoelectric ceramic powder and preparation method thereof

    CN101857436A